Designing an instrument for gamified community-based application using critical analysis: Preliminary study - Suhaila Jaffar; Aslina Baharum (MNNF Publisher, 2021)
The purpose of the paper is to study an instrument of gamification framework. This study focuses on gamification in e-learning, especially in early education; the ‘what’ and ‘how’ gamification can support e-learning within a community context. Gamification has taken someone popularity in the past few years in research in the context of education and business marketing. It has also gained interest from academics, educators, health management, employee engagement, civic engagement, and innovation. Gamification is an established practice and industry segment. Thus, because of the lack of children's engagement in the learning process and lack of motivation to learn, incorporating gamification has been acknowledged. It is hoped that these instruments will be useful for future research and the development of community learning applications using gamification.